FAKTOR PENYEBAB TERJADINYA ALIH KODE DAN CAMPUR KODE PADA MODEL KOMUNIKASI ETNIS JAWA DI DESA BALUNG LOR - ivashovia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language as a vital tool in humans communication activities easily develops. The influence of social mobility, education, economy, religion, social media, and politics became the beginning of the development of social language in society. The desire to understand each other’s intentions and purposes when communicating is the hope of every language user. Then everything will be done to achieve the desired goal. As in the Javanese ethnic communication model in Balung Lor village, as a minority group the Javanese ethnic community tries to understand, learn the language of the majority in Balung Lor village. As a result of this process of understanding and learning, it can unwittingly change the communication model of the Javanese ethnic community in Balung Lor village. Insertion of words in another language ( code mixing) and switching to another language ( code switching) are often carried out to achieve the goal of understanding the meaning of a communication with different ethnicities. To find out the factors causing code switching and code mixing in the Javanese ethnic communication model in Balung lor village. The researchers carried out all research procedures such as; observation, interviews, and direct involvement between research subjects. Analyzed using descriptive qualitative methods in order to make it easier for the study.